Bokeloh bat lyssavirus isolation in a Natterer's bat, Poland. (9th September 2018) - Smreczak, Marcin; Orłowska, Anna; Marzec, Anna; Trębas, Paweł; Müller, Thomas; Freuling, Conrad M.; Żmudziński, Jan F.
Abstract: In recent years, Bokeloh bat lyssavirus (BBLV), a member of the novel lyssavirus genus Bokeloh bat lyssavirus in the family Rhabdoviridae, has been detected in Germany (five cases) and France (two cases). Here, we report the isolation of BBLV in a Natterer's bat ( Myotis nattereri ) in Poland. The bat brain tested positive for rabies using classical diagnostics tests (FAT and RTCIT) and then subsequently confirmed by molecular techniques. Viral RNA was found in all peripheral organs tested, and the highest viral loads were detected in brain, the salivary gland and bladder. Phylogenetic analysis performed on complete viral genome sequences revealed the closest homology to representatives of BBLV lineage B, isolated previously in southern Germany. This case provides further evidence that BBLV is widespread in Europe.